Early vs. Late Initiation of Hemodialysis: Early Initiation as a Life-Saving Option in Stage III Leptospirosis Induced Acute Kidney Injury - Probowirasmi, Prasasti; Arifin; Aliyah Roselyn, Nadiya; Helmi Fakhruddin (Indonesian Journal of Medicine, 2026)
Background: Leptospirosis is a zoonotic disease endemic in tropical regions with a high burden among low-income populations. Its clinical spectrum ranges from mild illness to severe Weil’s disease, which may involve multiple organs with common and severe complication is acute kidney injury (AKI) with no specific therapy exists. In this report, we describe how early hemodialysis may improve outcomes. Case Presentation: A 60-year-old man presented with a 10-day history of fever. He also reported calf pain and jaundice that had appeared one week prior to admission. Over the past week, the patient experienced decreased urinary frequency, with urine becoming more concentrated in color. Laboratory tests revealed thrombocytopenia, leukocytosis, elevated SGOT and SGPT levels, hyperbilirubinemia, and azotemia. Leptospira IgM was positive. Urinalysis demonstrated proteinuria and bilirubinuria. The patient’s Modified Faine’s Criteria score was 34, and his SOFA score was 11. Results: Patient was diagnosed with Weil's disease with AKI III complicated by sepsis. The furosemide stress test was administered to the patient but the results was not favorable therefore hemodialysis was initiated leading to an improvement in the patient’s condition. Conclusion: Early initiation of hemodialysis in patients with leptospirosis induced AKI provides favorable immediate outcome and prevents them from falling into uremic syndrome leading to mortality.